Analisis Motivasi Kerja dan Kinerja Karyawan Divisi Marketing pada PT. BPRS Fajar Sejahtera Bali - Diki, Diki; Kusjuniati, Kusjuniati; Iswahyuni, Iswahyuni (STAI Denpasar Bali, 2023)
Motivation in a company is very important to be able to move all the power and limits of human capabilities and other facilities. The right motivation will be able to advance and develop the company. The problem of motivation in a company is the responsibility of management to create, organize and implement it, so management must be able to create motivation that is able to foster people's motives so that they want to act according to the company's wishes. The objectives of this study are: 1). Knowing the work motivation of employees of the marketing division at PT. BPRS Fajar Sejahtera Bali. 2) Knowing the performance of the employees of the marketing division at PT. BPRS Fajar Sejahtera Bali. This research method is descriptive qualitative. Data collection techniques, namely observation, interviews and documentation. The informants in this study were the Head of Marketing Division and eight marketing staff at PT. BPRS Fajar Sejahtera Bali, the procedure for determining informants by means of purposive sampling. Marketing division at PT. BPRS Fajar Sejahtera Bali has the following motivations: There is a work environment that has a positive influence on employees, there is protection and security provided by the company in the form of BPJS Health and Employment, and the company provides a form of recognition or respect for employees who excel and have company leaders who are competent in their fields, 2) Marketing division at PT. BPRS Fajar Sejahtera Bali has the following motivations: There is a work environment that has a positive influence on employees, there is protection and security provided by the company in the form of BPJS Health and Employment, and the company provides a form of recognition or respect for employees who excel and have company leaders who are competent in their fields, 2) Employee performance of the marketing division of PT. BPRS Fajar Sejahtera Bali still has not reached the company standards presented, employees are still not optimal in carrying out their duties and responsibilities.